Otentisitas Hadis dan Bantahan Harald Motzki atas Skeptisisme Orientalis terhadap Hadis - Hafidz, Nur Fiatin (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2023)
As the second source, the tradition has its own magnet to get people’s attention. Studies of tradition are often investigated by all circles, either insider or outsider. Nevertheless, orientalists’ study is not certainly as objective as the study of tradition Muslim scholars. The resulted thought must be sceptic for its being built on a negative impression on tradition. It can be demonstrated that most orientalists who did a scientific work to the tradition inferred that tradition is not authentic. But along with the era development, there appeared a different point of view. Some new orientalists who did more open-minded study on tradition presented, such as Harald Motzki. He is an orientalist who has a significant role in journey of tradition study. Through analytical descriptive method, this article means to serve the methodology of Harald Motzki on tradition and his criticisms to the previous sceptic scholars. It results that Harald Motzki could break his predecessor’s theories with his own theory; dating and isnad cum matn analysis. He strikes back at the sanad criticism of Ignaz Goldziher and Joseph Schacht and common link and family-isnad criticism of G.H.A. Juynboll. Besides, he also contributes to bear next scientific tradition studies. As an example, isnad cum matn theory is much borrowed to identify the tradition quality so far.